Proceedings of the Conference on Policy Instruments for Safeguarding Forest Biodiversity Legal and Economic Viewpoints. The Fifth International BIOECON Conference 15th 16th January 2004, House of Estates, Helsinki - (:unkn) unknown (Finnish Forest Research Institute, 2004)
The fifth seminar of the EU project Biodiversity and Economics for Conservation (BIOECON) was held in Helsinki, Finland, on the 15th 16th January 2004. The seminar was hosted by the Finnish Forest Research Institute (Metla) and the Institute of International Economic Law (KATTI) with assistance from the Forest Economics Forum of the Finnish Society of Forest Science. Under the heading Policy Instrument for Safeguarding Forest Biodiversity Legal and Economics Viewpoints, the seminar focussed on the implementation of biodiversity policies in the forest sector. This publication is a collection of papers presented in the workshop, with an addition of a few BIOECON papers related to the topic of the seminar.
Photo editor: Susan Tönnes
Photographs: Erkki Oksanen, Finnish Forest Research Institute, Vantaa Research Centre
Layout: Maija Heino, Finnish Forest Research Institute, Vantaa Research Centre
Keywords: metsä; metsäpolitiikka; monimuotoisuuden suojelu; politiikkainstrumentit; biodiversity conservation; forest; forest policy; policy instruments